Multidisciplinary Vulvar Cancer Management: The Dermatologist’s Perspective - Marta Cebolla-Verdugo; Victor Alfredo Cassini-Gómez de Cádiz; Juan Pablo Velasco-Amador; María Zulaika-Lloret; Francisco Manuel Almazán-Fernández; Ricardo Ruiz-Villaverde (Life)
Vulvar cancer, particularly squamous cell carcinoma (SCC) and melanoma, poses significant diagnostic and therapeutic challenges due to its complex presentation and high rates of postoperative complications. Effective management requires a multidisciplinary approach, integrating the expertise of gynecologic oncologists, dermatologists, plastic surgeons, and other specialists. This review highlights the dermatologist’s role in supporting early diagnosis, addressing predisposing conditions such as lichen sclerosus, and managing postoperative wound complications, including surgical site infections and dehiscence. Through two clinical cases, we illustrate how dermatological expertise complements surgical efforts by employing advanced wound care techniques such as negative pressure wound therapy and tailored dressing protocols. By collaborating closely with gynecologists and other team members, dermatologists enhance patient outcomes, ensuring timely recovery and the prevention of long-term sequelae. The article also discusses recent advances in treatment guidelines and targeted therapies, underscoring the importance of integrated care for optimizing patient outcomes in vulvar cancer.